Taá¹bÄ«qÄt Taâ€™lÄ«m al-Lughah al-Arabiyah li al-NÄá¹iqÄ«n bi al-Ê¿Arabiyah wa bi GhairihÄ al-Raqmiyah fÄ« MadÄrÄ«s al-ImÄrÄt al-Waá¹aniyah: Kaifiyatu IdÄrah Ê¿UrÅ«á¸ihÄ wa TaghziatihÄ al-RÄjiÊ¿ah - El Wahab, Ahdab Abd (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Applications of teaching Arabic to native and non-Arabic speakers in Emirates National Schools: how to manage their offerings and what is their feedback. Emirates National Schools strive to keep pace with technical progress and consider the rapid knowledge development in the light of the knowledge economy, in various educational and learning fields, especially in the field of teaching Arabic to native speakers and others. In this research, we will try to monitor experiences and experiences in this regard, to benefit from them in improving the digital performance of teaching Arabic to non-native speakers, aiming to: introduce the smart applications used in schools and manage their educational offerings, and indicate the characteristics of the supporting applications in order to identify the learnerâ€™s tasks and performance and how to provide feedback.ØªØ³Ø¹Ù‰ Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¥Ù…Ø§Ø±Ø§Øª Ø§Ù„ÙˆØ·Ù†ÙŠØ© Ù„Ù…ÙˆØ§ÙƒØ¨Ø© Ø§Ù„ØªÙ‚Ø¯Ù… Ø§Ù„ØªÙ‚Ù†ÙŠ ÙˆÙ…Ø±Ø§Ø¹Ø§Ø© Ø§Ù„ØªØ·ÙˆØ± Ø§Ù„Ù…Ø¹Ø±ÙÙŠ Ø§Ù„Ù…ØªØ³Ø§Ø±Ø¹ ÙÙŠ Ø¸Ù„ Ø§Ù‚ØªØµØ§Ø¯ Ø§Ù„Ù…Ø¹Ø±ÙØ©ØŒ ÙÙŠ Ù…Ø®ØªÙ„Ù Ø§Ù„ØÙ‚ÙˆÙ„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© ÙˆØ§Ù„ØªØ¹Ù„Ù‘ÙÙ…ÙŠØ©ØŒ Ø®Ø§ØµØ© ÙÙŠ Ù…Ø¬Ø§Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ ÙˆØ¨ØºÙŠØ±Ù‡Ø§ ÙÙ‚Ø¯ Ø£Ù†Ø´Ø£Øª Ø¹Ø¯Ø¯Ø§Ù‹ Ù…Ù† Ù…Ù†ØµØ§Øª Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø§Ù„Ø£Ø¬Ù‡Ø²Ø© Ø§Ù„Ø°ÙƒÙŠØ© Ù„Ø°Ù„ÙƒØŒ ÙˆØ§ÙƒØªØ³Ø¨ Ù…Ø¹Ù„Ù…ÙˆÙ‡Ø§ Ø®Ø¨Ø±Ø© ÙÙŠ Ø§Ù„Ø¥Ø¹Ø¯Ø§Ø¯ ÙˆØ§Ù„ØªÙ†ÙÙŠØ° ÙˆØ§Ù„ØªÙ‚ÙˆÙŠÙ… ÙˆØ§Ù„ØªØ·ÙˆÙŠØ±ØŒ ÙˆØ³Ù†ØØ§ÙˆÙ„ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø±ØµØ¯ Ø§Ù„Ø®Ø¨Ø±Ø§Øª ÙˆØ§Ù„ØªØ¬Ø§Ø±Ø¨ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„ØµØ¯Ø¯ ØŒÙ„Ù„Ø¥ÙØ§Ø¯Ø© Ù…Ù†Ù‡Ø§ ÙÙŠ ØªØ¬ÙˆÙŠØ¯ Ø§Ù„Ø£Ø¯Ø§Ø¡ Ø§Ù„Ø±Ù‚Ù…ÙŠ Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ØŒ Ù‡Ø§Ø¯ÙÙŠÙ† Ø¥Ù„Ù‰: Ø§Ù„ØªØ¹Ø±ÙŠÙ Ø¨Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø§Ù„Ø°ÙƒÙŠØ© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ ÙˆØ¥Ø¯Ø§Ø±Ø© Ø¹Ø±ÙˆØ¶Ù‡Ø§ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ©ØŒ ÙˆØ¨ÙŠØ§Ù† Ø³Ù…Ø§Øª Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§Øª Ø§Ù„Ø¯Ø§Ø¹Ù…Ø© Ø¨ØºØ±Ø¶ Ø§Ù„ÙˆÙ‚ÙˆÙ Ø¹Ù„Ù‰ Ù…Ù‡Ù…Ø§Øª Ø§Ù„Ù…ØªØ¹Ù„Ù… ÙˆØ£Ø¯Ø§Ø¦Ù‡ ÙˆÙƒÙŠÙÙŠØ© Ø§Ù„ØªØºØ°ÙŠØ© Ø§Ù„Ø±Ø§Ø¬Ø¹Ø© ÙˆÙ…Ø§ Ù„Ø§Ø²Ù… Ø°Ù„Ùƒ Ù…Ù† Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ§Øª ÙˆØ³Ù„Ø¨ÙŠØ§Øª.